Relationship of Customer Relationship Learning to Service Quality of Regional Development Banks - Aji, Bondan Seno; Ujianto, Ujianto; Nugroho, Mulyanto (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
This study aims to analyze the relationship between customer relationship learning and service quality at Bank Pembangunan Daerah Jawa Timur Plc, Surabaya Region. This research uses quantitative methods with a descriptive research approach. The population was 1,329 savings customers in 10 locations of the Bank Pembangunan Daerah Jawa Timur Plc network in the Surabaya region, representing the eastern, western, northern and southern regions of Surabaya with 307 respondents.The results showed that customer relationship learning had an effect on the quality of PT Bank Pembangunan’s service. The area of East Java Plc in the Surabaya area, this shows that with a customer relationship learning strategy, it will be able to increase service quality. Service quality is the totality of the characteristics of goods and services that demonstrate its ability to satisfy customer needs.